Host adaptation and microbial competition drive Ralstonia solanacearum phylotype I evolution in the Republic of Korea. Issue 11 (5th November 2020) - Prokchorchik, Maxim; Pandey, Ankita; Moon, Hayoung; Kim, Wanhui; Jeon, Hyelim; Jung, Gayoung; Jayaraman, Jay; Poole, Stephen; Segonzac, Cécile; Sohn, Kee Hoon; McCann, Honour C.
Abstract : Bacterial wilt caused by the Ralstonia solanacearum species complex (RSSC) threatens the cultivation of important crops worldwide. We sequenced 30 RSSC phylotype I ( R. pseudosolanacearum ) strains isolated from pepper ( Capsicum annuum ) and tomato ( Solanum lycopersicum ) across the Republic of Korea. These isolates span the diversity of phylotype I, have extensive effector repertoires and are subject to frequent recombination. Recombination hotspots among South Korean phylotype I isolates include multiple predicted contact-dependent inhibition loci, suggesting that microbial competition plays a significant role in Ralstonia evolution. Rapid diversification of secreted effectors presents challenges for the development of disease-resistant plant varieties. We identified potential targets for disease resistance breeding by testing for allele-specific host recognition of T3Es present among South Korean phyloype I isolates. The integration of pathogen population genomics and molecular plant pathology contributes to the development of location-specific disease control and development of plant cultivars with durable resistance to relevant threats.